치과의사의 서번트 리더십이 조직문화와 치과위생사의 행복지수에 미치는 영향 - 김나연; Na-yeon Kim; 배현숙; Hyeon-suk Bae; 강유민; Yu-min Kang (Han'guk Ch'iwisaeng Hakhoe chi, 2018)
Objectives: The purpose of this study was to examine how the dentist’s servant leadership affects the happiness index of dental hygienists. Methods: The subjects were 221 dental hygienists that have been working at dental clinics or dental hospitals. The data were analyzed using SPSS Version 20.0 (IBM Co., Armonk, NY, USA). An independent t-test and one-way ANOVA analysis were conducted to examine the difference in the happiness index of dental hygienists according to general characteristics. The independent t-test was conducted to examine organizational culture and happiness index according to upper and lower group based on the mean score for servant leadership. Pearson’s correlation analysis was used to examine the correlation among key factors. Multiple regression analysis was conducted to identify factors influencing the happiness index of dental hygienists. Results: According to the analysis, there was a statistically significant positive correlation between the dentist’s servant leadership, the organizational culture and the happiness index of dental hygienists. However, a stewardship of the dentist’s servant leadership factors was not found to have any correlation with the market culture. A multiple regression analysis was performed after including the dentist’s servant leadership, the organizational culture and the happiness index of dental hygienists. Meanwhile, the stewardship and community-building effect of the dentist’s servant leadership had a statistically significant effect on the happiness index of dental hygienists. Consequently, a higher servant leadership factor in dentists was correlated with a higher happiness index of dental hygienists. Conclusions: The findings show that the dentist’s servant leadership affect the happiness index of dental hygienists. Therefore, effective intervention and education programs related to the dentist’s servant leadership and sound organizational culture are necessary to enhance dental hygienists’ happiness index. Additionally, a follow-up study will determine the causal relationship among the dentist’s servant leadership, the organizational culture and the happiness index of dental hygienists, considering organizational members and the environment of the dental clinics.